The Influence Of Strategic Leadership And Servant Leadership On Competitive Advantage Mediated By Strategic Planning In Manufacturing Companies In Bekasi District - Fitri, Tasya; Retno Purwani Setyaningrum (Jurnal Ekonomi, 2024)
Thie main focus of this study is to find the impact of the influence of strategic leadership and servant leadership on competitive advantage mediated by strategic planning. Data were collected using the Google formular, and data processing software called SmartPLS was used. The results of this study are positive and significant, the variables of that strategic leadership has a significant effect on competitive advantage, meanwhile several variables that have no effect include strategic leadership has no effect on strategic planning, servant leadership has no effect on competitive advantage, strategic planning as a mediating variable has no significant effect on competitive advantage, strategic planning has no effect significantly to competitive advantage, servant leadership does not significantly influence strategic planning, strategic planning as a mediating variable does not significantly influence competitive advantage. Results of the mediation analysis reveal that strategic planning plays a role in the correlation between strategic leadership and servant leadership and has an impact on competitive advantage This research is expected to help manufacturing companies and employee performance.